La auditoría tributaria como herramienta en la prevención de contingencias tributarias en la empresa Konexa Track & Systems S.A.C. de la ciudad de Trujillo en el año 2015 - Hernandez Saira, Christian Adan (2017)
The present research work has the purpose of applying the Tax Audit through an analysis of the current situation of the company regarding the fulfillment of its tax obligations which will positively influence the prevention of tax contingencies in the year 2015. According to the analysis made to the company Konexa Track & Systems S.A.C. And based on the application of interview through a questionnaire to the manager of the company, it has been determined that the company does not correctly apply the current tax rules. The development of this research work is to demonstrate that the Tax Audit as a tool influences positively the prevention of tax contingencies in the Company Konexa Track & Systems S.A.C. Of the city of Trujillo in the year 2,015, whose activity is the marketing and installation of global positioning systems - GPS, being prepared for any tax inspection by the National Superintendence of Customs and Tax Administration - SUNAT. For this purpose, a study of the economic and financial information, books, records and affidavits of the company will be carried out in order to identify the existing risks by carrying out an analysis of the legal norms that the company is obliged to comply with by applying the The interview with the Manager to contrast it with reality. Thus, the results show omissions with respect to the General Tax on Sales and Income Tax, for not depositing the drawdowns and not using the means of payment in those vouchers that exceed the limit of banking, in addition to having identified fines and interest Which were not added to the Income in the year, in this way the new taxable amount of the General Tax on Sales and Income Tax, their respective repairs, interests and fines, is determined; Determining the debt as of December 31, 2015. In this regard, we recommend that the company applies the Preventive Tax Audit as a policy and acts within the legal framework complying with its tax obligations.